Exploring the Anticancer Activity of Artocarpus heterophyllus Leaves: Selective Effects on Triple-Negative Breast Cancer and HPV16-Positive Tumorigenic Cells - Ariana Cabrera-Licona; Gustavo A. Hernández-Fuentes; Oscar F. Beas-Guzmán; Alejandra E. Hernández-Rangel; Janet Diaz-Martinez; Osval A. Montesinos-López; José Guzmán-Esquivel; Víctor H. Cervantes-Kardasch; Mario Ramírez-Flores; Alejandrina Rodriguez-Hernandez; Erika R. González-Espinosa; Ana B. Castellanos-Gutiérrez; et al. (Life)
Artocarpus heterophyllus (jackfruit) is widely distributed in subtropical and tropical regions, and some phytochemicals isolated from this species have demonstrated anti-proliferative effects. However, its impact on triple-negative breast cancer (TNBC) and HPV-related cervical cancer models remains unclear. This study evaluated the phytochemical profile and anticancer activity of an ethanolic extract from A. heterophyllus leaves (AHEE) in the TNBC cell line MDA-MB-231 and in the HPV-16+ murine cancer cell line TC-1. Phytochemical screening and spectroscopic analyses (UV-Vis, IR, 1H, and 13C NMR) revealed the presence of tannins, alkaloids, steroids, coumarins, and flavone-type flavonoids, with a total phenolic content of 3.34 µg GAE/mg and flavonoid content of 0.44 mg QE/g extract. In 2D cultures, AHEE reduced cell viability by 49% in TC-1 and 24% in MDA-MB-231 at 300 µg/mL, inhibited colony formation and migration in TC-1, and impaired survival but not migration in MDA-MB-231. In 3D cultures, 250 µg/mL inhibited proliferation, migration, and anchorage-independent growth in both cell lines. Furthermore, the combination of AHEE with one-fifth of the IC50 of doxorubicin or cisplatin produces an effect comparable to that observed with the full IC50 of these drugs. These findings suggest that AHEE possesses anticancer activity with cell-type-specific effects and highlight its potential as an adjuvant therapy. Further studies are warranted to elucidate its mechanisms of action.